2011
DOI: 10.4028/www.scientific.net/kem.488-489.476
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Crack Propagation in New Generation Aluminium Alloys

Abstract: The fatigue crack propagation behaviour of a new third generation Al-Cu-Li alloy type 2050-T84 developed for aeronautical applications is studied in comparison to a new generation Al-Cu-Mg alloy type 2022-T851. The alloy resistance against crack growth is shown to depend on alloy composition, aging condition and atmosphere environment. The crack path and the growth rate at moderate DK and in the near-threshold domain are discussed in terms of the slip morphology with respect to the microstructure. The differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Aluminum alloys are considered cost-effective metallic materials for aeronautical applications due to their low density, high strength/density ratio, and good corrosion resistance [1], [2]. Density and weight reduction are critical in the aeronautical industry due to fuel price and environmental concerns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminum alloys are considered cost-effective metallic materials for aeronautical applications due to their low density, high strength/density ratio, and good corrosion resistance [1], [2]. Density and weight reduction are critical in the aeronautical industry due to fuel price and environmental concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue crack propagation (FCP) studies of alloy AA2050-T84 compared with AA7050 in air and saline environments showed that the former presented a retarded crystallographic propagation during stage I of crack propagation, which was ascribed to the barrier effect of grain boundaries [1]. The crack closure effect persisted in stage II for the AA2050-T84 alloy, while it was not observed for the AA7050-T7451 alloy [11].…”
Section: Introductionmentioning
confidence: 99%
“…Grain structure: Both unrecrystallized (UnRX) and recrystallized (RX) sheet and plate are produced, depending on the alloys and property requirements. Highly elongated grains in recrystallized AA 2199 sheet and partially recrystallized AA 2050 plate are mentioned by Rioja and Liu (2012) and Richard et al (2012), respectively, and appear to be regarded as typical or normal. Highly elongated grains in recrystallized AA 2199 sheet and partially recrystallized AA 2050 plate are mentioned by Rioja and Liu (2012) and Richard et al (2012), respectively, and appear to be regarded as typical or normal.…”
Section: Review and Discussion Of Available Information For Third-genmentioning
confidence: 99%
“…3,4 Aluminum alloys are considered cost-effective materials for aeronautical applications due to their low density, high specific strength and good corrosion resistance. 5,6 Material selection is of major importance to increase fatigue life, therefore high strength and fracture toughness materials are desired, such as the AA7050-T7451, exceeding the 7075-series alloys in strength properties and corrosion resistance. The AA7050 are commonly used in internal structures, such as wings and fuselage attachments.…”
Section: Introductionmentioning
confidence: 99%